2014
DOI: 10.1287/opre.2014.1279
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Rescheduling with Cruise Speed Control

Abstract: Airline operations are subject to frequent disruptions typically due to unexpected aircraft maintenance requirements and undesirable weather conditions. Recovery from a disruption often involves propagating delays in downstream flights and increasing cruise stage speed when possible in an effort to contain the delays. However, there is a critical trade-off between fuel consumption (and its adverse impact on air quality and greenhouse gas emissions) and cruise speed. Here we consider delays caused by such disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…We first tested our model on a problem instance used in a recent work by Aktürk et al (2014). The instance is called Single Hub Data as the flight network is formed by considering aircraft that originate their first flight from Chicago O'Hare International Airport (ORD) and revisit ORD at least once during the same day.…”
Section: Results For Single Hub Datamentioning
confidence: 99%
“…We first tested our model on a problem instance used in a recent work by Aktürk et al (2014). The instance is called Single Hub Data as the flight network is formed by considering aircraft that originate their first flight from Chicago O'Hare International Airport (ORD) and revisit ORD at least once during the same day.…”
Section: Results For Single Hub Datamentioning
confidence: 99%
“…where ρ ≥ 0. As in Aktürk et al (5), we let ζ = 1.5 in our computational experiments. It is important to note that the US costs might differ from the ones provided in the EUROCONTROL [28].…”
Section: 2mentioning
confidence: 99%
“…Therefore, if a flight is delayed, swapping the aircraft provides robustness by allowing a flight with high demand to be flown. Aktürk et al [5] use the idea of swapping aircraft between flights to reduce the effect of a disruption on the schedule. They provide approximately 30% cost savings compared to the delay propagation recovery approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive overview of early contributions can be found in Ball et al (2007), while more recent surveys can be found in Barnhart et al (2012), Bianco et al (2006) and Pellegrini and Rodriguez (2013). We observe that, while the coordination issue is often referred to multi-airport coordination, as in Aktürk et al (2014) or Andreatta et al (2011), this paper focuses on coordination of operations in a single airport. In the latter context, Balakrishnan andChandran (2010), andSölveling et al (2010) focus on the runway scheduling, Artiouchine et al (2008), Hu and Chen (2005), and Di Paolo (2008,2009) focus on the landing scheduling from airspace resources to runways, while other authors deal with the coordination of the TCA airspace and the runways (landing and take-off scheduling), e.g., D'Ariano et al (2012D'Ariano et al ( , 2015, Lieder and Stolletz (2016), Murça and Müller (2015), Samà et al (2013Samà et al ( , 2014Samà et al ( , 2015.…”
Section: Introductionmentioning
confidence: 99%